Impact of micro-fins on a heated cylinder submerged in a nanofluid saturated medium. (October 2021) - Mahdavi, Mostafa; Sharifpur, Mohsen; Aybar, Hikmet S.; Chamkha, Ali J.; Meyer, Josua P.
Highlights: Nanofluid pool boiling on a horizontal cylinder with and without various numbers of fins has numerically studied. The correlations for nucleate site density and bubble diameter were implemented according to nanoparticles. Discrete phase modelling was used to track the location of nanoparticles on the cylinder. The aspect ratios of the fins played a major role in heat transfer compared to the number of fins. Heat transfer was improved for nanofluids with volume fractions less than 1%. Abstract: Flow and thermal features of nanofluid pool boiling on a circular heat sink with mirco-fins attached were numerically investigated. The initial geometry consisted of a horizontal cylinder with an outside diameter of 20 mm submerged in a saturated water/nanofluid for validation cases. Physical micro-fins with various configurations were added to the outside surface of the cylinder for the purpose of this study. Due to the presence of nanoparticles, three phases were considered in modelling as liquid, vapour and particles. Unsteady Eulerian- Eulerian from multiphase two-phase flow approach was combined with wall boiling model to identify the heat and mass transfer at the hot surface, as well as interaction forces between the liquid and vapour phases. For the case of nanofluid, thermo-physical properties were modified based on particles concentration. To track the fate of nanoparticles, discrete phase modelling was employed from the Lagrangian frame. To solve the boiling heat transfer at the hot surface and fins, nucleate site density and bubbles diameter were modified and implemented to account for the presence of nanoparticles and corrected roughness. All the equations were discretised and solved by CFD commercial software, ANSYS-Fluent v19.5. The results showed that the impacts of fin aspect ratio on heat transfer are higher compared to the number of fins. However, the role of these geometrical parameters decreased as the nanofluid concentration increased. In addition, it was found that the best enhancement in heat transfer was obtained for nanofluid volume fraction around 1% vol.